2001
DOI: 10.1086/323085
|View full text |Cite
|
Sign up to set email alerts
|

Influenza Vaccine Effectiveness in Preventing Hospitalizations and Deaths in Persons 65 Years or Older in Minnesota, New York, and Oregon: Data from 3 Health Plans

Abstract: This study developed methods and determined the impact of influenza vaccination on elderly persons in 3 large health plans: Kaiser Permanente Northwest, HealthPartners, and Oxford Health Plans. Data for the 1996-1997 and 1997-1998 seasons were extracted from administrative databases. Subjects were health plan members > or = 65 years old. Comorbid conditions collected from the preceding year were used for risk adjustment with logistic regression. The virus-vaccine match was excellent for year 1 and fair for yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
106
0
3

Year Published

2003
2003
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 226 publications
(117 citation statements)
references
References 26 publications
(38 reference statements)
8
106
0
3
Order By: Relevance
“…These findings agree with a recent large study among elderly members of three HMOs followed during the 1996/97 and 1997/98 influenza A epidemics [28]. The estimate of 159 persons that need to be vaccinated to prevent one serious outcome was somewhat higher than in the large HMO study (102 persons).…”
Section: Discussionsupporting
confidence: 89%
“…These findings agree with a recent large study among elderly members of three HMOs followed during the 1996/97 and 1997/98 influenza A epidemics [28]. The estimate of 159 persons that need to be vaccinated to prevent one serious outcome was somewhat higher than in the large HMO study (102 persons).…”
Section: Discussionsupporting
confidence: 89%
“…According to a meta-analysis of 20 cohort studies, published between 1974 and 1992, the pooled estimate of the efficacy of the vaccine was: 56% for prevention of respiratory illness; 53% for prevention of pneumonia; 50% for prevention of hospitalisation overall; and 68% for prevention of death [274]. Recent large cohort studies of the elderly in the community have confirmed these findings, demonstrating efficacy rates between 20-80% in the prevention of hospitalisation for influenza and pneumonia, 40% in the prevention of congestive heart failure, and 40-70% in the prevention of death overall [275][276][277][278][279][280]. There are also data indicating that the absolute risk reduction is 2-5 times higher among high-risk persons than among healthy elderly persons [281].…”
Section: Prevention By Vaccinationmentioning
confidence: 99%
“…46 The importance of dose-sparing is most evident in high-surge situations, such as in pandemic 47 and seasonal flu, 48,49 where large populations are at risk and a new set of strains can be required each year. 50 Dose sparing is also important in increasing capacity and reducing the expense of a vaccine dose, especially in cost-sensitive globalhealth indications where the price of the vaccine limits its use and coverage, as in the case of polio.…”
Section: Benefits Of Id Vaccinationmentioning
confidence: 99%